Analisis Penggunaan Bahasa Indonesia dalam Jurnalistik pada Media Massa Online - Suprihatma Suprihatma (Journal on Education, 2024)
This writing aims to explain the use of Indonesian in journalism. Various news languages have their own characteristics which are called news language styles. Journalistic language is the language used by journalists (journalists) when writing news articles in the mass media. In practice, there are still some mass media that do not comply with linguistic rules in reporting. There are three possibilities that cause this: First, journalists lack knowledge and understanding of linguistic rules; secondly, journalists pay less attention to the use of good words. and appropriate language rules. Third, Indonesian and journalists do not comply with applicable language rules.This research uses a descriptive qualitative research approach with the data collection techniques used are documentation techniques and hermeneutic techniques. In this research, the validation technique The data source in this research is the main news published in the October 2023 edition. The data collected in this research is in the form of words or sentences so that the research results are aimed at revealing findings in the form of descriptions. The sample in this study was 10 (ten) detik.com news stories.The results of the research by taking ten examples of articles show that there are still errors such as the use of inappropriate words in the news, errors in writing verbs, there is a waste of words, there are inconsistencies in the use of language. However, there are also articles that are good and meet language rules. So it can be concluded that there are still some articles that still need to pay attention to language rules to avoid mistakes in writing news.